Women with fear of childbirth might benefit from having a known midwife during labour. Issue 1 (February 2019) - Hildingsson, Ingegerd; Karlström, Annika; Rubertsson, Christine; Haines, Helen
Abstract: Aim: Having a known midwife at birth is valued by women across the world, however it is unusual for women with fear of childbirth to have access to this model of care. The aim of this study was to describe the prevalence and factors related to having access to a known midwife for women referred to counseling due to childbirth fear. We also wanted to explore if women's levels of childbirth fear changed over time. Methods: A pilot study of 70 women referred to counseling due to fear of birth in 3 Swedish hospitals, and where the counseling midwife, when possible, also assisted during labour and birth. Results: 34% of the women actually had a known midwife during labour and birth. Women who had a known midwife had significantly more counseling visits, they viewed the continuity of care as more important, were more satisfied with the counseling and 29% reported that their fear disappeared. Fear of birth decreased significantly over time for all women irrespective of whether they were cared for in labour by a known midwife or not. Conclusions: Although the women in the present study had limited access to a known midwife, the results indicate that having a known midwife whom the women met on several occasions made them more satisfied with the counseling and had a positive effect on their fear. Building a trustful midwife–woman relationship rather than counseling per se could be the key issue when it comes to fear of birth.